Vibration serviceability evaluation of lightweight cold-formed steel floor systems. (April 2022) - Zhang, Sigong; Xu, Lei
Abstract: Featured by lightweight and high strength-to-weight ratio, cold-formed steel framing has been increasingly used in floor systems of low-rise and mid-rise residential and commercial building constructions. The high stiffness-to-weight ratio and low damping of such floor systems may result in potential risk for annoying floor vibrations and then bring forth a serviceability issue, particularly in an attempt to achieve longer floor spans. Several design methods have been published to enable engineers to ensure human comfort on wood-framed and structural steel-framed floors. However, although significant advancement has been attained in cold-formed steel framing, a practical and efficient design method of evaluation vibration serviceability for cold-formed steel floor systems is yet available. This paper presents a simplified design method for vibration serviceability of lightweight cold-formed steel floor systems, in which a new acceptance criterion for vibration serviceability was proposed by using binary logistic regression to correlate human prediction on floor vibration performance with vibration characteristics of the floor systems based on available test data. The procedure and corresponding equations for computing design parameters which signify the vibration characteristics of the floor system are presented. Two examples are provided to demonstrate efficiency of the proposed design method.